Money, Gold, and Income in the United States, 1921-32 - Currie, Lauchlin (Quarterly Journal of Economics, 1933)
I. Description of method of compilation of an annual series of money, 77.— II. Reliability of various banking series as indexes of change in the money supply, 87.— III. Money supply amenable to Federal Reserve control, 88.— IV. Time deposits, 89.— V. Money, incomes and income velocities, 91.— VI. Money and gold, 92.